Analysis of The Physicochemical and Sensory Quality of Adee Cake During Storage - Ismail Sulaiman; Syarifah Rohaya; Muhammad Ichsan (Elkawnie, 2022)
Abstract: Cake is a wet food product made by baking dough from flour, sugar, eggs, milk, fat, and other additives. Adee cake is one of the typical foods marketed in the Pidie area, which is very famous and becomes one of the foods as souvenirs. The problem faced with this cake is the shelf life and quality of the cake. Therefore, this research was carried out about the physicochemical properties of Adee cake during the storage process and to observe the sensory properties. This study used a completely randomized design (CRD) with a non-factorial pattern, namely storage time consisting of (0, 1, 2, 3, and 4 days) with three repetitions. Further tests of DMRT will follow the analysis of variance ANOVA in this study. The results of the hardness analysis obtained an average of 51.43 gf. The color analysis showed that the average coefficient value was 111 on the top and 252 on the inside showing a very significant difference. Chemical analysis obtained the average, namely, water content 39.30%, ash content 0.79%, fat content 7.94%, protein content 1.82%, crude fiber content 0.70%, and carbohydrates 49.76%, showed a very significant difference (P≤0.01). The organoleptic test analysis (hedonic) obtained the average, namely, color 3.63, texture 3.29, flavor 3.64, taste 3.30, and overall 3.46 showed a very significant difference (P≤0.01).Abstrak: Cake merupakan salah satu produk makanan semi-basah yang dibuat dengan pemanggangan adonan dari tepung, gula, telur, susu, lemak dan bahan tambahan lainnya. Cake adee ini merupakan salah satu makanan khas yang dipasarkan di daearah Pidie, yang sangat terkenal dan menjadi salah satu makanan sebagai oleh-oleh, problem yang dihadapi pada cake ini adalah masa simpan dan kualitas dari kue tersebut, oleh karena itu dilakukan penelitian tentang  sifat fisikokimia kue Adee selama proses penyimpanan dan mengamati sifat sensorisnya. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan pola non faktorial yaitu lama penyimpanan yang terdiri dari (0, 1, 2, 3, dan 4 hari) dengan tiga kali pengulangan. Selanjutnya uji DMRT akan mengikuti analisis varians ANOVA pada penelitian ini. Hasil analisis kekerasan diperoleh rata-rata 51,43 gf, hasil analisis warna menunjukkan nilai koefisien rata-rata 111 pada bagian atas dan 252 pada bagian dalam menunjukkan perbedaan yang sangat signifikan. Analisis kimia diperoleh rata-rata kadar air 39,30%, kadar abu 0,79%, kadar lemak 7,94%, kadar protein 1,82%, kadar serat kasar 0,70%, dan karbohidrat 49,76%, menunjukkan perbedaan yang sangat nyata (P≤0,01). Uji organoleptik (hedonik) diperoleh rata-rata yaitu warna 3,63, tekstur 3,29, rasa 3,64, rasa 3,30, dan keseluruhan 3,46 menunjukkan perbedaan yang sangat nyata (P≤0,01).